Exergy Analysis of Coal-Based 2 X 7 MW Steam Power Plant - Hermawan, Indra; Idris, Muhammad; Wibisono, Anggih Prasetyo; Satria, Habib (International Journal of Electrical, Energy and Power System Engineering, 2023)
In this study, an analysis was conducted on a steam power plant system with a capacity of 2 x 7 MW based on coal. The coal fuel used by the majority of refined sizes is not in accordance with the recommendations of the American Society of Mechanical Engineers (ASME). The main objective of the study was to analyze the system components separately and to measure the exergy value of the components, covering the electrical energy so that it is known which equipment experiences the greatest energy loss as well as knowing the efficiency value of the equipment used. Efficiency and exergy are calculated using plant operation data. The results of the study found that the largest exergy destruction occurred in boilers, meaning that there was the largest energy loss in this section with a value of 37.34 MW (16.71%), while the destruction of the smallest exergy occurred in condensers of 0.58 MW (99.24%).